Reação de genótipos e híbridos de tomateiro à Meloidogyne enterolobii - Rosa, Juliana Magrinelli Osório (2014)
The diseases caused by root-knot nematodes on tomato have been considered as the most dangerous for this crop. This research aimed to study the reaction of ten tomato hybrids (Absoluto, Cascade, Cordillera, Donatto, Ellen, Fascínio, Laura, Marguerita, Nícolas and Sanni) and two genotypes (05 tom0041 and 08 tom00345) to M. enterolobii. The experiments were developed out separately in a greenhouse and BOD (25°C). The substrate inoculation was made with 5,000 eggs and second stage juveniles of M. enterolobii. The variables gall and egg mass indexes, final population and the reproduction factor were determined 60 days after inoculation. On both experiments, all the genotypes and hybrids were susceptible to M. enterolobii.